Effect of spray - strake on manoeuvring performance of a planing hull patrol vessel [compact disc] - 355731 Andi Haris Muhammad; Adi Maimun Abdul Malik (2008)
Thesis (Doktor Falsafah (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2008